Understanding the Effects of Remote Work on Employee Well-being and Organizational Outcomes: A Multimethod Approach in the Context of COVID-19 - Adam Chati; Amine HAMDOUNE; Sara Yassine; Salah KOUBAA; Rachid Hachad; Hicham Nachit (African Scientific Journal, 2023)
In the context of the COVID-19 pandemic, where remote work has become widely adopted, this study aims to understand the effects of remote work on employee well-being and organizational outcomes. This study employs a multimethod approach to examine the relationships between technostress, work recovery, overall well-being, and organizational consequences among remote workers. A quantitative survey was administered to remote workers, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Additionally, qualitative interviews were conducted with human resource managers to gain in-depth insights into remote work experiences and practices during and after the pandemic. This study contributes to understanding the relationships between remote work, employee well-being, and organizational outcomes in the context of the COVID-19 pandemic. The findings emphasize the importance of managing technostress, promoting work recovery, and fostering interpersonal and intrapersonal well-being to enhance engagement and organizational resilience.